2011–2020 trends of urban and regional ammonia in and around Barcelona, NE Spain. (October 2022) - Reche, C.; Pérez, N.; Alastuey, A.; Cots, N.; Pérez, E.; Querol, X.
Abstract: It is well established that in environments where NH3 abundance is limiting in secondary PM2.5 generation, a reduction of NH3 emissions can result in an important contribution to air quality control. However, as deduced from open data published by the European Environmental Agency, the availability of measurements of NH3 concentrations is very scarce, with very few countries in Europe reporting data consistently for extensive periods, this being especially true for urban background sites. In this framework, simultaneous multi-site measurements were carried out in NE (Northeast) Spain from 2011 to 2020, using diffusion tubes. The highest NH3 concentrations were recorded at the traffic site (5.3 μgm −3 on average), followed by those measured at the urban background site (2.1 μgm −3 ). Mean concentrations at the mountain site were 1.6 μgm −3, while the lowest concentrations were recorded at the regional site (0.9 μgm −3 ). This comparison highlights traffic emissions as an important source of NH3 . A statistically significant time trend of this pollutant was observed at the urban background site, increasing by 9.4% per year. A season-separated analysis also revealed a significant increasing trend at the mountain site during summer periods, probably related with increasing emissions from agricultural/livestock activities. These increases in NH3 concentrations were hypothesized to be responsible for the lack of a decreasing trend of NO3 − concentrations at the monitoring sites, in spite of a markedly reduction of NO2 during the period, especially at the urban background. Thus, this would in turn affect the effectiveness of current action plans to abate fine aerosols, largely made up of secondary compounds. Actions to reduce NH3 concentrations at urban backgrounds are challenging though, as predicting NH3 is subjected to a high uncertainty and complexity due to its dependence on a variety of factors. This complexity was clearly indicated by the application of a decision tree algorithm to find the parameters better predicting NH3 at the urban background under study. O3, NO, NO2, CO, SO2 and OM + EC concentrations, together with meteorological indicators, were used as independent variables, obtaining no combination of parameters evidently able to predict significant differences in NH3 concentrations, with a coefficient of determination between real and predicted measurements lower than 0.50. This emphasizes the need for highly temporally and spatially resolved NH3 measurements for an accurate design of abatement actions. Graphical abstract: Image 1 Highlights: Availability of NH3 measurements in urban environments is scarce in Europe. A ten-year dataset on multi-site NH3 concentrations in NE Spain was evaluated. NH3 concentrations ranged between 0.9 and 5.3 μgm −3, with the highest at the traffic site. Concentrations increased over time at the urban and the mountain sites, especially during summers. Increases in NH3 may be responsible for the lack of a decreasing trend of NO3 −, despite NO2 reductions.